2007
DOI: 10.1088/0264-9381/24/18/005
|View full text |Cite
|
Sign up to set email alerts
|

Sound speeds, cracking and the stability of self-gravitating anisotropic compact objects

Abstract: Using the the concept of cracking we explore the influence of density fluctuations and local anisotropy have on the stability of local and non-local anisotropic matter configurations in general relativity. This concept, conceived to describe the behaviour of a fluid distribution just after its departure from equilibrium, provides an alternative approach to consider the stability of selfgravitating compact objects. We show that potentially unstable regions within a configuration can be identified as a function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
363
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 639 publications
(386 citation statements)
references
References 41 publications
11
363
1
Order By: Relevance
“…Cracking was introduced by Herrera [110] as a possibility of breaking of perturbed selfgravitating spheres. Abreu et al [111] found a simple requirement for avoiding this to happen, namely that the region of stability be…”
Section: Conditions For a Physically Realistic Modelmentioning
confidence: 99%
“…Cracking was introduced by Herrera [110] as a possibility of breaking of perturbed selfgravitating spheres. Abreu et al [111] found a simple requirement for avoiding this to happen, namely that the region of stability be…”
Section: Conditions For a Physically Realistic Modelmentioning
confidence: 99%
“…The physically reasonable interior solutions of a NS should satisfy several energy conditions [10,11,12]. The corresponding energy conditions are described as follows.…”
Section: And the Lagrangian Density For Free Leptons Ismentioning
confidence: 99%
“…The recent investigation on the properties of anisotropic compact stars are reported for examples in Reference [8,2,3]. In general, physical meaningful anisotropic fluid equation of state (EOS) should follow general physical energy conditions [10,11,12]. So far energy condition analysis for anisotropic fluid is investigated only for the case compact objects which are described by polytropes type of EOS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations